2000
DOI: 10.1086/315695
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin‐Resistant and Methicillin‐SusceptibleStaphylococcus aureusin the Community

Abstract: Recent reports indicate that community-acquired methicillin-resistant Staphylococcus aureus (MRSA) infections are increasing and may now involve persons without risk factors predisposing for acquisition. To estimate the extent of community MRSA in New York City, the prevalence of S. aureus and MRSA nasal colonization in a well-patient population of 500 children and guardians was determined. The prevalence of S. aureus nasal carriage was 35% for children and 28% for guardians. One person with predisposing risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
107
4
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(130 citation statements)
references
References 12 publications
12
107
4
7
Order By: Relevance
“…9%. These levels of carriage are similar to those reported in community studies elsewhere [12][13][14][15]. The chosen sample site of the anterior nares has been demonstrated to have the highest sensitivity to detect carriage in the absence of infected wounds [20].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…9%. These levels of carriage are similar to those reported in community studies elsewhere [12][13][14][15]. The chosen sample site of the anterior nares has been demonstrated to have the highest sensitivity to detect carriage in the absence of infected wounds [20].…”
Section: Discussionsupporting
confidence: 82%
“…5%) [12]. This frequency was similar to that obtained from studies performed in the United States, Portugal and Italy, all of which reported carriage rates of less than 1 % [13][14][15]. Although the importance of the community as a source of MRSA infections has not been determined, this change in pattern of occurrence may require modifications in hospital infection control programmes.…”
Section: Introductionsupporting
confidence: 84%
“…Previously MRSA was largely confined to health-care settings and its acquisition associated with established risk factors [4]. More recently, it has spread into the community (community-associated MRSA, CA-MRSA), and been implicated in reports of severe infections in otherwise healthy persons [5][6][7]. Exposure to health care, including surgery, immunosuppression, antibiotic use, and long-term hospitalization, and healthcare workers (HCWs) is recognized as a risk factor for hospital-associated MRSA colonization [6,8,9], but further work is required to identify reservoirs for CA-MRSA in the community, and their importance as a source of strains imported into the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Existe otro grupo de sujetos que no tiene el dato de haber estado internado previamente, pero tiene el antecedente de haber visitado en un hospital a un paciente infectado por MRSA, o de haber recibido a un familiar portador de MRSA en casa, luego de su alta hospitalaria (31). Aquí se debe considerar persona de riesgo al familiar de un personal de salud.…”
Section: Mrsa En La Comunidadunclassified
“…Un estudio hecho en la comunidad en la que evaluó 500 sujetos de la comunidad con hisopado nasal y se asiló 162 cepas portadores nasales de Estafilococo, encontrándose solo 1 cepa de MRSA, y este fue un sujeto con antecedente de haberse internado previamente en un hospital (31).…”
Section: Mrsa En La Comunidadunclassified